Spray Deposited Nanostructured CuO Thin Films: Influence of Substrate Temperature and Annealing Process - Zare Asl,Hassan (2018)
In this study, CuO thin films were deposited on glass substrates at a wide range of temperatures from 450ºC to 550ºC with steps of 25ºC by chemical spray pyrolysis technique. Aiming to investigate the effect of annealing process, one of the resulting films was annealed at 450ºC for 3 hours under ambient air. Based on X-ray diffraction, all the resulting films are monoclinic with two prominent peaks at ~36º and ~39º. The crystallite size of the CuO film deposited at 450ºC was found to be the largest in comparison with the others. As the substrate temperature increased, a gradual change was observed for the CuO thin film surface morphology and in the case of annealed film, the grains and their boundaries became indistinguishable. The resistivity of the films was reduced by virtue of increasing the substrate temperature and also, both the mobility and carrier concentration of the annealed film were improved drastically after annealing. As expected, the CuO thin films absorption was considerable in the visible region and gradually declined after 800nm. The estimated band gap value of the CuO film deposited at 450ºC were fairly close to the optimum band gap for solar applications.